2007
DOI: 10.1634/stemcells.2006-0236
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of Embryonal Carcinoma 2102Ep As a Reference for Human Embryonic Stem Cell Research

Abstract: As the number of human embryonic stem cell (hESC) lines increases, so does the need for systematic evaluation of each line's characteristics and potential. Comparisons between lines are complicated by variations in culture conditions, feeders, spontaneous differentiation, and the absence of standardized assays. These difficulties, combined with the inability of most labs to maintain more than a few lines simultaneously, compel the development of reference standards to which hESC lines can be compared. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 44 publications
(62 reference statements)
7
118
0
1
Order By: Relevance
“…Northern blot and cloning analysis identified several microRNAs in human ESC, several of which were identical to microRNAs previously reported in mouse ESC [143]. We recently reported that several microRNAs are highly expressed across multiple hESC lines [144]. Furthermore, as these cells differentiate, the microRNA profiles change significantly.…”
Section: Micrornas In Embryonic and Adult Stem Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…Northern blot and cloning analysis identified several microRNAs in human ESC, several of which were identical to microRNAs previously reported in mouse ESC [143]. We recently reported that several microRNAs are highly expressed across multiple hESC lines [144]. Furthermore, as these cells differentiate, the microRNA profiles change significantly.…”
Section: Micrornas In Embryonic and Adult Stem Cellssupporting
confidence: 73%
“…Using Northern blot analysis, cloning, or array methods, a set of microRNAs specific to pluripotent cell types, such as mouse ES cells [35], mouse or human embryonic carcinoma cells [22], or human ESC [32,[143][144][145], has been identified. Although these studies could not yet ascribe regulatory functions to these microRNA populations, the unique presence of these populations in stem cells and their disappearance during differentiation suggest roles in maintaining "stemness" by suppressing pluripotency and/or restricting cell differentiation.…”
Section: Micrornas In Embryonic and Adult Stem Cellsmentioning
confidence: 99%
“…(B) Enhanced p21 levels in Tera 24 hours after treatment with synthetic anti-miR-106b seed family members. Synthetic anti-miR-220 was used as negative control, since miR-220 expression was not detectable in TC (32). (C) Differences in p21 enhancement in EC cells 24 hours after synthetic anti miR-17-5p treatment.…”
Section: Figurementioning
confidence: 99%
“…Previously, miRNA expression has been examined in murine and human ES cells using cloning, microarray, quantitative polymerase chain reaction (PCR), and deep sequencing technologies on selected cell lines [20][21][22][23][24][25][26][27][28][29]. These studies typically involve embryoid body (EB) formation as an intermediate step, and the differentiation protocols extend for several weeks.…”
Section: Establishment Of Induced Pluripotent Stem (Ips) Cell Linesmentioning
confidence: 99%